Emergencies and Politics : A Sober Hobbesian Approach / [electronic resource] - Sorell, Tom (Cambridge : Cambridge University Press, 2013)
In this book Tom Sorell argues that emergencies can justify types of action that would normally be regarded as wrong. Beginning with the ethics of emergencies facing individuals, he explores the range of effective and legitimate private emergency response and its relation to public institutions, such as national governments. He develops a theory of the response of governments to public emergencies which indicates the possibility of a democratic politics that is liberal but that takes seriously threats to life and limb from public disorder, crime or terrorism. Informed by Hobbes, Schmitt and Walzer, but substantially different from them, the book widens the justification for recourse to normally forbidden measures, without resorting to illiberal politics. This book will interest students of politics, philosophy, international relations and law.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Democracy; Liberalism; Rule of law